Chest Pain: The Need to Consider Less Frequent Diagnosis - Pedro Magalhães; Anabela Morais; Sofia Carvalho; Joana Cunha; Ana R. Lima; J. Ilídio Moreira; Trigo Faria (Case Reports in Cardiology)
Chest pain is one of the most frequent patient’s complaints. The commonest underlying causes are well known, but, sometimes, in some clinical scenarios, it is necessary to consider other diagnoses. We report a case of a 68-year-old Caucasian male, chronically hypertensive, who complained of recurrent episodes of chest pain and fever with elevated acute phase reactants. The first investigation was negative for some of the most likely diagnosis and he quickly improved with anti-inflammatory drugs. Over a few months, his symptoms continued to recur periodically, his hypertension was aggravated, and he developed headaches and lower limbs claudication. After a temporal artery biopsy that was negative for vasculitis, he underwent a positron emission tomography suggestive of Takayasu Arteritis. Takayasu Arteritis is a rare chronic granulomatous vasculitis of the aorta and its first-order branches affecting mostly females up to 50 years old. Chest pain is experienced by >40% of the patients and results from the inflammation of the aorta, pulmonary artery, or coronaries.